Abnormal Complement Activation and Inflammation in the Pathogenesis of Retinopathy of Prematurity - Rathi, Sonika; Jalali, Subhadra; Patnaik, Satish; Shahulhameed, Shahna; Musada, Ganeswara R.; Balakrishnan, Divya; Rani, Padmaja K.; Kekunnaya, Ramesh; Chhablani, Preeti Patil; Swain, Sarpras; Giri, Lopamudra; Chakrabarti, Subhabrata; et al. (Frontiers in Immunology, 2017)
Retinopathy of prematurity (ROP) is a neurovascular complication in preterm babies, leading to severe visual impairment, but the underlying mechanisms are yet unclear. The present study aimed at unravelling the molecular mechanisms underlying the pathogenesis of ROP. A comprehensive screening of candidate genes in preterms with ROP (n=189) and No-ROP (n=167) was undertaken to identify variants conferring disease susceptibility. Allele and genotype frequencies, linkage disequilibrium and haplotypes were analysed to identify the ROP-associated variants. Variants in CFH (p=2.94x10-7), CFB (p=1.71x10-5), FBLN5 (p=9.2x10-4), CETP (p=2.99x10-5), and CXCR4 (p=1.32x10-8) genes exhibited significant associations with ROP. Further, a quantitative assessment of 27 candidate proteins and cytokines in the vitreous and tear samples of babies with severe ROP (n=30) and congenital cataract (n=30) was undertaken by multiplex bead arrays and further validated by western blotting and zymography. Significant elevation and activations of MMP9 (p=0.038), CFH (p=2.24x10-5), C3 (p=0.05), C4 (p=0.0013), Il-1ra (p=0.00187), VEGF (p=0.0027) and G-CSF (p=0.0099) proteins were observed in vitreous of the babies with ROP suggesting an increased inflammation under hypoxic condition. Along with inflammatory markes, activated macrophage/microglia were also detected in the vitreous of ROP babies that secreted complement component C3,VEGF,Il-1rα and MMP-9 under hypoxic stress in a cell culture model.Increased expression of the inflammatory markers like the Il-1rα (p=0.014), MMP2 (p=0.0085) and MMP-9 (p=0.03) in the tears of babies at different stages of ROP further demonstrated their potential role in disease progression. Based on these findings, we conclude that increased complement activation in the retina/vitreous in turn activated microglia leading increased inflammation. A quantitative assessment of inflammatory markers in tears could help in early prediction of ROP progression and facilitate effective management of the disease, thereby preventing visual impairment.